PENGARUH IMPLEMENTASI MEKANISME TATA KELOLA PERUSAHAAN TERHADAP PROFITABILITAS DENGAN KEPEMILIKAN PEMERINTAH SEBAGAI VARIABEL MODERATING PERUSAHAAN BUMN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Iza, Maria; Edastami, Mayangsari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research was written with the aim of determining the size of the board of commissioners, independent commissioners, and audit committee on profitability with government ownership as a moderating variable for state-owned enterprises in 2019-2022. This type of research is a causal study that is cause and effect. The type of data used in this study is quantitative data in the form of data on the size of the board of commissioners, independent commissioners, audit committee, government ownership, and profitability. The data source in this study is financial reports found on the Indonesia Stock Exchange (IDX) for 2019-2022 for a period of 4 years. The population in this study is state-owned enterprises listed on the IDX. The sample in this study is 26 companies. The sampling technique used in this study is non-probability sampling. The results of this study show that the size of the board of commissioners, independent commissioners, and audit committee have a positive effect on profitability. Meanwhile, government ownership successfully moderates (strengthens) the influence of the size of the board of commissioners and independent commissioners on profitability. However, government ownership does not successfully weaken the influence of the audit committee on profitability.